2015
DOI: 10.1177/0363546515594449
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors Affecting Rotator Cuff Healing After Arthroscopic Repair in Small to Medium-sized Tears

Abstract: In small to medium-sized rotator cuff tears, grade II fatty degeneration of the infraspinatus muscle according to the Goutallier classification could be a reference point for successful healing, and anatomic outcomes might be better if repair is performed before the patient is 69 years old and the tear size exceeds 2 cm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
120
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(124 citation statements)
references
References 45 publications
2
120
1
1
Order By: Relevance
“…However, fatty infiltration of the supraspinatus does not seem to be a determinant factor in tendon healing. Park et al 55 did not find significant relationship between preoperative supraspinatus fatty infiltration and postoperative tendon healing. Contrarily, it seems that fatty infiltration of the infraspinatus and subscapularis is a highly significant factor (p<0.001).…”
Section: Resultsmentioning
confidence: 89%
“…However, fatty infiltration of the supraspinatus does not seem to be a determinant factor in tendon healing. Park et al 55 did not find significant relationship between preoperative supraspinatus fatty infiltration and postoperative tendon healing. Contrarily, it seems that fatty infiltration of the infraspinatus and subscapularis is a highly significant factor (p<0.001).…”
Section: Resultsmentioning
confidence: 89%
“…Although elderly patients generally have a greater incidence of rotator cuff disease (10), the incidence of rotator cuff surgery declined after the age of 70. Park et al (20) reported that the failure rate for RCR was significantly higher in patients aged > 69 years compared with those aged ≤ 69 years and retears of the rotator cuff are closely associated with advanced age (2122). Initial conservative treatments can be safely undertaken in older patients (> 70 years old) with chronic tears (4).…”
Section: Discussionmentioning
confidence: 99%
“…Most common system used to classify fatty degeneration of rotator cuff muscles was described by Goutallier et al [25]. Even small and medium tears are at risk for failure after repair with as little as grade 2 muscle degeneration [26]. Shoulders with more severe (grade 3 or 4) degeneration, where more than 50% of muscle volume is replaced by fat, are at a very high risk of poor outcomes, since, even if tendon repair and healing to bone is achieved, dynamic function of the rotator cuff muscle-tendon unit remains compromised.…”
Section: Outcomes Of Rotator Cuff Repairmentioning
confidence: 99%